Sharia compliance in aqiqah digital transactions: A case study of Elsyifa Akikah SME - Asyari, Mohamad Maula; Aditya, Mochammad Yana; Octaviano, Dicky (Junal Ilmu Manajemen, 2026)
The rapid development of digital technology has transformed transaction systems across business sectors, including religious services such as aqiqah. This study analyses Sharia principles implementation in the digital transaction system of Elsyifa Akikah SME using a qualitative case study design. Data were collected from 20 purposively-selected informants via in-depth interviews, participatory observation, document analysis, and a Likert-scale consumer survey (n=30); analysed through reflexive thematic analysis (Braun et al., 2022), generating 180 initial codes and four themes (inter-coder reliability: kappa=0.81). Findings show the SME implements salam, ijarah, and wakalah contracts that fulfil fiqh muamalah rukun and syarat. The novel ru'yah hukmiyyah digital mechanism live video call for virtual animal inspection effectively eliminates gharar, evidenced by zero cancellations across 1,350+ transactions since 2016. Consumer satisfaction averaged 4.3/5; 85% reported high perceived Sharia compliance; 90% indicated repurchase intent. Key constraints include implicit rather than explicit ijab-qabul and absence of formal external Sharia audit. This study contributes the concept of ru'yah hukmiyyah digital as a contemporary fiqh adaptation, with implications for DSN-MUI fatwa development and SME Sharia governance frameworks.